Малогабаритна спіральна антена - Ільницький, Л.Я.; Щербина, О.А.; Михальчук, І.І. (Моделювання та інформаційні технології, 2010)
In modern systems of mobile radiomonitoring the antennas of small dimensions are used. These antennas are ineffective in the ranges of high and very high frequency, as it is difficult to match them with the feeder due to low effective length and low input resistance.